Glucocorticoid receptor concentrations and terminal transferase activity as indicators of prognosis in acute non-lymphocytic leukaemia. Issue 6279 (6th June 1981) - Skoog, L; Nordenskjöld, B; Ost, A; Andersson, B; Hast, R; Giannoulis, N; Humla, S; Hägerström, T; Reizenstein, P
Abstract : Activity of terminal deoxynucleotidyl transferase (TdT), adenosine deaminase, and 5'nucleotidase and the cellular concentration of glucocorticoid (dexamethasone) receptor were determined in 25 patients with acute non-lymphocytic leukaemia. All patients were treated according to a common protocol. Increased activity of TdT (greater than 0.1 unit/microgram DNA) was found in 11 patients. This group of patients was shown to have higher remission and survival rates (p = 0.06) compared with patients with low activity of TdT. The glucocorticoid receptor concentration of the leukaemic blast cells ranged from 0 to 0.94 fmol/microgram DNA. Thirteen patients had blast cells with a glucocorticoid receptor concentration over 0.22 fmol/microgram DNA. These patients had significantly increased remission and survival rates (p = 0.006) compared with those with a low receptor concentration. This finding cannot be explained by a difference in sensitivity to glucocorticoids since these were not used as therapeutic agents. Adenosine deaminase and 5'nucleotidase activities both varied within two orders of magnitude. No correlation could be found between activities of these enzymes and remission or survival rate. These results show that measurements of TdT activity and the glucocorticoid receptor concentration yield valuable prognostic information in acute non-lymphocytic leukaemia.